Nova proposta para rápida formação/combate dos produtos de glicação avançada (AGES) e propriedades farmacológicas de Hancornia speciosa Gomes - Marques, Samuel Pedro Dantas (2017)
This study reports the development of methodologies for formation and combat possibilities to Advanced Glycation Products (AGEs), and evaluate the chemical constitution and pharmacological properties of Hancornia speciosa Gomes(HSG). Regarding the obtaining of the AGEs, considering in vitro procedures, the current methodologies need an incubation period of up to 4 weeks. The methods developed in this work allowed a significant reduction of the reaction time (48 hours-glucose and fructose tests) (3 hours-tests with glyoxal and methylglyoxal), due to the coupling to the free radical generation system called hypoxanthine/xanthine oxidase. Thus, the methodologies presented in this work consisted in promoting the reaction between sugar solutions (glucose, fructose), or dicarbonyl compounds (methylglyoxal, glyoxal), with bovine serum albumin (BSA) protein solution, using different reaction media. The enzyme xanthine oxidase (XO) was added to the system in order to promote the formation of AGEs in a reaction environment with excess hydroxyl free radicals (.OH). The presence of these radicals in excess during the glycation and glycooxidation of the protein indicate to have promoted the oxidation of the chain of amino acid residues thereof, as well as sugars, thus giving α-dicarbonyl derivatives (glyoxal and methylglyoxal) more rapidly, the which made possible the significant reduction of the time of formation of the AGEs. The higher reactivity of fructose to glucose, to producer AGEs, was present in all conditions evaluated. The ability of different chemical species to combat the glycation process, acting as capture agents of α-dicarbonyl species, was shown to be effective for aminoguanidine (standard indicated in the literature), methanolic extracts of HSG leaves and rutin. The rutin was more active for the capture of dicarbonyl species than the standard indicated by the literature, due to the formation of more stable mono and/or disubstituted adducts. The measurement of the formation/combat of AGEs was determined by spectrofluorimetry. The qualitative analysis by high performance liquid chromatography coupled to a mass spectrometer (HPLC-DAD-ESI-MS) of HSG methanolic extracts showed a great variety of polyphenolic compounds (phenolic acids and flavonoids), confirming the potential as a source of bioactive compounds. In the leaves and bark, the greatest number of polyphenolic compounds were verified when compared to the fruits. The following species were identified for the first time in HSG: vanillic acid glucoside, 3,4-dihydroxybenzoic acid, para-hydroxybenzoic acid, vanillin, trans-para-coumaric acid; cis-para-coumaric acid, trans-ferulic acid quinate, trans-ferulic acid, cis-ferulic acid, cis-ethyl chlorogenic acid, trans-ethyl chlorogenic acid, quercetin, quercetin pentoside, quercetin glucoside, quercetin rhamnoside, quercetin galactoside, quercetin rhamnogalactoside, quercetin rhamnoglucocoumarate, quercetin rhamnogalactocoumarate, kaempferol rhamnoglucoside, kaempferol rhamnogalactoside, kaempferol rhamnoglucocoumarate, kaempferol rhamnogalactocoumarate, isorhamnmetin rhamnoglucoside, afzelechin-C-glucoside. For the values of the antioxidant potential and inhibition of angiotensin I (antihypertensive effect), leaves and bark extracts were more active, presenting promising IC50 values when compared to the synthetic form of vitamin E (Trolox). The capacity of HSG extracts to inhibit the action of the enzyme acetylcholinesterase, which is related to Alzeimer treatment, has been shown to be quite significant for the hexane bark extract (EHC). The fractionation of the same, led to obtaining a mixture as a more active fraction. Through the use of magnetic resonance and literature data, the presence of lupeol in this fraction was identified.